Predict Anterior Cruciate Ligament Injury In Elite Male Soccer Players? Focus On The Five Factors Maximum Model (International Journal of Physiotherapy, 2021)
Background: For years, the rupture of the anterior cruciate ligament (ACL) has been a feared injury in young soccer players since it causes physiological and psychological changes while incurring significant economic losses.Methods: Through clinical research, understanding the mechanisms and identifying risk factors has enabled sports and performance professionals to establish robust models to predict and reduce the risk of ACL injury. Developments in medical devices also allow a more precise, more objective assessment and improve the traceability of the various quantitative and qualitative parameters necessary to detect the risk of ACL injury.Results: While general preventive protocols have shown evidence for an overall reduction in injury, there are still limitations regarding ACL injury. Therefore, we can collect personalized data from these models and the variables involved, predict, prevent, and program performance throughout the season. Additionally, the multi-professional team supervising the athlete must establish a close relationship centered on feeling and listening to the player who remains in control of his performance.Conclusion: Let the players decide on their career and not an injury.